2021
DOI: 10.33774/chemrxiv-2021-h06nc-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Divergent Stereochemical Outcomes in the Insertion of Donor/Donor Carbenes into the C–H Bonds of Stereogenic Centers

Abstract: Intramolecular C-H insertions with donor/donor dirhodium carbenes provide a concise and highly stereoselective method to set two contiguous stereocenters in a single step. Herein, we report the insertion of donor/donor carbenes into stereogenic carbon centers allowing access to trisubstituted benzodihydrofurans in a single step. This study illuminates, for the first time, the stereochemical impact on the carbene center and delineates the structural factors that enable control over both stereogenic centers. Ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…136,137 However, Shaw and coworkers have found that donor/donor carbenes can undergo two-step, stepwise C-H insertions, 138 or exist at the borderlands 139 of concerted and stepwise. 140 Finally, dissociation of product 4 from weakly bound complex 9 regenerates catalyst 3. It is unclear whether axial solvent ligation is relevant at any point in this catalytic cycle (Figure 1, outer green circle versus inner blue circle).…”
Section: Overall Approachmentioning
confidence: 99%
“…136,137 However, Shaw and coworkers have found that donor/donor carbenes can undergo two-step, stepwise C-H insertions, 138 or exist at the borderlands 139 of concerted and stepwise. 140 Finally, dissociation of product 4 from weakly bound complex 9 regenerates catalyst 3. It is unclear whether axial solvent ligation is relevant at any point in this catalytic cycle (Figure 1, outer green circle versus inner blue circle).…”
Section: Overall Approachmentioning
confidence: 99%
“…Metal-carbene mediated chemistry has a long and winding history. 10 Our group has worked independently and collaborated closely with experimental groups to understand mechanisms of Rh-carbene mediated transformations, including C-H insertion 64,65 and ylide formation reactions, [66][67][68] with the aim of developing synthetically useful models of reactivity and selectivity. This chemistry has proven to be a playground of its own-a family of synthetically relevant organometallic reactions that display behaviors considered by some to be esoteric, but which play important roles in determining product distributions.…”
Section: Semibullvalene In Historical Contextmentioning
confidence: 99%
“…137,138 However, Shaw and coworkers have found that donor/donor carbenes can undergo two-step, stepwise C-H insertions, 139 or exist at the borderlands 140 of concerted and stepwise. 141 Finally, dissociation of product 4 from weakly bound complex 9 regenerates catalyst 3. It is unclear whether axial solvent ligation is relevant at any point in this catalytic cycle (Figure 1, outer green circle versus inner blue circle).…”
Section: Overall Approachmentioning
confidence: 99%